2002
DOI: 10.1089/108729102753429389
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and the Desire to Quit Among Individuals Living with HIV

Abstract: Among individuals living with human immunodeficiency virus (HIV), studies have found that smokers are at greater risk than nonsmokers to develop bacterial pneumonia, oral lesions and acquired immune deficiency syndrome (AIDS) dementia complex. Information is lacking re garding the prevalence of cigarette smoking among people living with HIV or about their in tentions to quit smoking. A survey was conducted with a sample of patients attending an HIV outpatient clinic at San Francisco General Hospital to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
4
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 10 publications
10
135
4
1
Order By: Relevance
“…1 By contrast, between 50% and 70% of PLWHA smoke cigarettes daily. 3,5,[10][11][12][13] On a positive note, one longitudinal study showed that smoking rates may be declining among women with HIV (to 39% in 2011 in the Women's Interagency HIV Study). 14 Although the reasons for this high prevalence are not well understood, there are some factors that appear to distinguish nonsmoking from smoking PLWHA.…”
Section: Prevalence Of Smoking Cessation In Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…1 By contrast, between 50% and 70% of PLWHA smoke cigarettes daily. 3,5,[10][11][12][13] On a positive note, one longitudinal study showed that smoking rates may be declining among women with HIV (to 39% in 2011 in the Women's Interagency HIV Study). 14 Although the reasons for this high prevalence are not well understood, there are some factors that appear to distinguish nonsmoking from smoking PLWHA.…”
Section: Prevalence Of Smoking Cessation In Hivmentioning
confidence: 99%
“…Recent studies reveal that nearly two-thirds of HIV+ smokers wish to quit smoking. [3][4][5] However, despite the high-risk nature of smoking among PLWHA, relatively few studies have systematically examined treatment efforts to reduce smoking in this population. This dearth of studies might be a result of the nature of HIV/AIDS as an illness.…”
Section: Introductionmentioning
confidence: 99%
“…19,24 Current smoking has been reported in 40% to 70% of HIV-positive patients, two-to three-fold greater than the general population. 4,22,[25][26][27][28][29][30][31] Compared with non-smokers, smokers have a two-fold or greater increased risk of MI 19 and CVD. 24,32 Although two studies have reported decreasing rates of smoking over time, in part suggesting that in an aging cohort, smoking rates are decreasing, 4,5 few data are available on actual rates of smoking as HIV-positive patients age.…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…Several reasons have been suggested, including social conditions, polysubstance abuse, psychiatric comorbidities, physical and mental distress, lack of access to smoking cessation interventions and adherence to such treatments. 27,29,104 Pilot data have shown that existing smoking cessation interventions are feasible in HIV care settings, [105][106][107] although these interventions have yet to be confirmed in large clinical trials. More research is needed to evaluate the efficacy and generalisability of smoking cessations programs in HIV-positive patients, and to gain a better understanding of the complex needs of HIV-positive patients, 108 as well as research on the potential interaction of pharmocotherapies and ART.…”
Section: Preventionmentioning
confidence: 99%
“…They found that over 70% of HIV positive outpatients smoked, and that 80% of that sample had not considered quitting (Niaura et al 2000). Similarly, Mamary et al (2002) found that 54% of outpatients with HIV smoked, but in contrast, found that 64% expressed some desire to quit. These rates of smoking are much higher than among the general population (21% prevalence), where 70% report wanting to quit; (CDC 2007).…”
Section: Introductionmentioning
confidence: 99%